Optimasi Lokasi Dan Stasiun Pemadan Kebakaran Di Kota Bangkinang - Hafid Akbar; Rian Tri Komara Iriana; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Kampar district is an area with growth rate, high migration and urbanization. The development of an increasing number of people have an impact on the movement system in Kampar district, particularly Bangkinang city. Crowd and narrow access roads and the installation of the portal, the number of vehicle and traffic congestion is a barrier in the acceleration speed fire fighting units to arrive at the disaster site. A complicating factor is the outage channel away hydran /water ways/ river around the fire scene. This study aim to creating an optimal plan to determine the location where the fire station was placed. Given the potential for fire is becoming increasingly significant, these hazards must be anticipated and faced with a variety preventionefforts are comprehensive, systematic, effective and sustainable. This research used quantitative methods that located in Bangkinang city start from Juni 2014. The study is done by considering the speed of the vehicle (35 km/hours, 40 km/hours, 50 km/hours), mileage and travel time (5 minute, 10 minuteand 15 minute. By doing 3 (three) simulations carried out the importance of the result of each simulations calculations on the importance of the total area of service for each simulations is 231,818 km2, 357,755 km2, and 440,075 km2. Variable in this study is the optimization of the location and the fire station in Bangkinang, and applying SIG to develop models of the relationship between the criteria determine the location of emergency fire fighting facilities. Data analysis techniques aresimulation models in the form of the application of remote sensing technology, spatial analysis and descriptive direction of determining the location of new fire station. The results of this research shows that optimization modelling that the location of the fire department made to get the location of fire station locations right to produce efficiency and effectiveness in handling fires. Done by designing a few posts on some areas the fire department are Bangkinang. Accordingliy, this modeling is expected to minimize the impact of losses incurred or the lost of life, property, damage of public infrastructure and other physicalbuilding.Keywords : optymal location,service area, fire station, network analyst